Effect of Package Type and Storage Duration on TBA Values of Shredded Eel - Kasumi A Polutu; Rieny Sulistijowaty; Faiza A Dali (The NIKe Journal, 2019)
This study aims to determine the effect of the type of packaging and storage time at room temperature on the quality of shredded eel (Anguilla sp.) Especially in TBA (Thiobarbituric acid). The main research used the experimental method. Especially to determine the TBA value using a Completely Randomized Design (CRD) 3 × 4 factorial and 2 replications. TBA value of shredded eel during storage increased. The results of the analysis with the use of different packages during storage have a very significant effect on the increase in TBA values. The highest TBA value in eel shredded for up to 56 days storage was TBA in plastic jars of 0.3849 mg / kg and the lowest in vacuum plastic packaging of 0.1439 mg / kg. Keywords: packaging; storage time; shredded; eel; Anguilla sp.; TBA; Thiobarbituric acid